Ion composition at comet 67P near perihelion: Rosetta observations and model-based interpretation - Heritier,KL; Altwegg,K; Balsiger,H; Berthelier,J-J; Beth,A; Bieler,A; Biver,N; Calmonte,U; Combi,MR; De,Keyser J; Eriksson,AI; Fiethe,B; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present the ion composition in the coma of comet 67P with newly detected ion species over the 28–37 u mass range, probed by Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA)/Double Focusing Mass Spectrometer (DFMS). In summer 2015, the nucleus reached its highest outgassing rate and ion-neutral reactions started to take place at low cometocentric distances. Minor neutrals can efficiently capture protons from the ion population, making the protonated version of these neutrals a major ion species. So far, onlyNH+4has been reported at comet 67P. However, there are additional neutral species with proton affinities higher than that of water (besides NH3) that have been detected in the coma of comet 67P: CH3OH, HCN, H2CO and H2S. Their protonated versions have all been detected. Statistics showing the number of detections with respect to the number of scans are presented. The effect of the negative spacecraft potential probed by the Rosetta Plasma Consortium/LAngmuir Probe on ion detection is assessed. An ionospheric model has been developed to assess the different ion density profiles and compare them to the ROSINA/DFMS measurements. It is also used to interpret the ROSINA/DFMS observations when different ion species have similar masses, and their respective densities are not high enough to disentangle them using the ROSINA/DFMS high-resolution mode. The different ion species that have been reported in the coma of 67P are summarized and compared with the ions detected at comet 1P/Halley during the Giotto mission.